An Introduction to Neural Networks - David Bisant (Proceedings of the International Florida Artificial Intelligence Research Society Conference)
This tutorial will cover an introduction to modern neural networks and how they are applied to problems in artificial intelligence. Basic terminology, history, application methods, and application case studies will be covered. Modern topics such as deep learning will be covered. The material will be filtered and summarized for the novice. Further reading and software packages and frameworks will also be discussed.